2003
DOI: 10.1023/a:1026197119569
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The objective of this study was to assess health related quality of life (QOL) in patients with type I diabetes mellitus (DMT1) and to compare their QOL with the QOL of persons of comparable age in the general population. Furthermore we wanted to investigate which factors mostly influence QOL. In a Dutch cohort of 281 patients with DMT1 QOL was assessed using two generic instruments: the EuroQol and the RAND-36. We performed regression analyses to investigate relationships between several demographic (e.g. sex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
1
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(28 citation statements)
references
References 32 publications
3
23
1
1
Order By: Relevance
“…The presence of complications has been reported to be associated with poorer quality of life [2, 4, 23, 24]. In our study, individuals who had incident cardiovascular disease showed greater declines in the physical component score.…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…The presence of complications has been reported to be associated with poorer quality of life [2, 4, 23, 24]. In our study, individuals who had incident cardiovascular disease showed greater declines in the physical component score.…”
Section: Discussionsupporting
confidence: 51%
“…The ultimate goal of the treatment for type 1 diabetes has been to achieve metabolic control to prevent the development of macro- and microvascular complications. Intensive glycemic control reduces these complications, but increases patient burden and may affect quality of life [1, 2]. The burdens of intensive glycemic control include inconvenience, discomfort, costs, and at least occasional hypoglycemia.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We adjusted the eGFR MDRD values for differences using the conventional Jaffe creatinine method before 2007 and the isotope-dilution mass spectrometrytraceable enzymatic creatinine method after 2007. HRQOL was assessed annually from 1995 to 2001, and these results were reported previously [12] . From 2001 onwards, HRQOL was assessed in 2002 and 2010.…”
Section: Measurement Of Clinical Data and Hrqolmentioning
confidence: 99%
“…The full study design has been published in detail previously [12] . In brief, from January 1995 to January 1996, consecutive visiting T1DM patients treated at the diabetes outpatient clinic of the Weezenlanden Hospital (currently Isala), Zwolle, The Netherlands, were invited to participate.…”
Section: Study Design and Populationmentioning
confidence: 99%